The Case of the Confused Giver - Joseph Hawley Murphy (Washington University Law Quarterly, 1952)
Although the federal gift, estate and income taxes are all part of the same revenue code, and in it the term "gift" frequently occurs, it does not mean the same thing for all purposes. It has to be considered in the particular context in which it appears, complicating the taxpayer's problem beyond all reason.
Keywords: Inheritance estate and gift taxes